Shortness of breath on a mustard patient: multidisciplinary approach improves outcomes - Isabella Casallas-Gutierrez; Tomas Chalela; Nestor Sandoval; Laura Acosta-Izquierdo; Julian Forero; Stephany Luna-Pisciotti; Carlos-Eduardo Guerrero-Chalela (Journal of Cardiothoracic Surgery)
Abstract Background Dextro-transposition of the great arteries post-atrial switch patients may experience complications like baffle stenosis. While percutaneous interventions are the standard treatment, severe calcification can require uncommon alternatives such as surgical redo procedures. Case presentation We present a 27-year-old female with a history of dextro-transposition of the great arteries corrected with an atrial switch at 11 months old who presented with shortness of breath. Imaging revealed severe superior baffle obstruction. Due to extensive baffle calcification, surgical reoperation with total baffle replacement was performed. The patient recovered well, with sustained symptomatic relief and normal biventricular function at follow-up. Conclusions This case underscores the importance of multimodal imaging for diagnosing complex baffle complications and the critical role of multidisciplinary teams in planning tailored interventions. Surgical redo remains viable in cases where percutaneous approaches are contraindicated, ensuring favorable outcomes in challenging scenarios.